Strategic behavior and organizational structure in religions - Donald Wittman (University of California, Economics Department, 2012)
Religions are organized in a variety of ways. They may resemble an elected autocracy, a parliamentary democracy, or something akin to a monarchy, where heredity plays a primary role. This variation allows for a comparative study of their organization. These differing power arrangements call for different types of strategic behavior in the fight for control over church doctrine and finance. And they also induce different institutional responses. I show where screening is highly institutionalized and when the age of a person may be an important strategic factor in choosing a leader. I am thus able to explain what otherwise would be very puzzling differences in the age of appointment across religions and within a particular religion, overtime. In a nutshell, this paper is about politics and strategic behavior in the large (democracy versus autocracy) within the context of the small (religious institutions).
Keywords: D02; D72; Z12; 330; religious organizations; autocracy; age; organizational structure; voting strategy